2017
DOI: 10.5530/ijper.51.2s.53
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration of Microspheres’ Capsules Based on Ethylcellulose and Synthesized Poly (Butylsuccinate) as Biodegradable Matrices for Drug Delivery of an Antithyroidian Agent

Abstract: Introduction:The present paper provides details of preparation of hardcapsules based on microspheres containing 2-aminothiazole as an antithyroidian agent and synthesized poly(butylsuccinate) (PBS) or ethylcellulose(EC10) as biodegradable matrices as well as the study of the drug delivery. Methods: A disintegration tests of these gelatinous capsules were done. The biodegradable synthesized polyester was characterized by infrared spectroscopy, nuclear magnetic resonance (mono and bidimentional H1NMR, 13CNMR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…In order to remove the residual monomers, the polymer obtained is heated at 200 °C in a 100 cc flask for three hours under high vacuum using a vacuum pump (max = 103 mm Hg). ( Chirani et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to remove the residual monomers, the polymer obtained is heated at 200 °C in a 100 cc flask for three hours under high vacuum using a vacuum pump (max = 103 mm Hg). ( Chirani et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The obtained microspheres were determined in triplate. Several mathematic formula (Kczmarski and Bellot, 2003;Chirani et al, 2017) were used to calculate different characteristic parameters such as: the mean diameters (d10, d32 and d43), size distribution, d10 number mean diameter, d32 the diameter of sauter, (the volumesurface mean), d43 the weight mean diameter (the volume mean diameters) (Eq. 4-6).…”
Section: Determination Of the Encapsulation Efficiencymentioning
confidence: 99%
“…These systems provide a pH-dependent drug release mechanism. [20][21][22] In drug microencapsulation, [23][24][25] the most used class of hydrophobic polymers is cellulose derivatives including ethyl cellulose (EC) and cellulose acetate butyrate (CAB) for a prolonged release. 26 Jelvehgari et al have shown that CAB formulations exhibit enough buoyancy to reside in the stomach over a prolonged and slower drug release.…”
Section: Introductionmentioning
confidence: 99%
“…The function of microcapsules into diversity therapeutic applications had led to the layout of many different microencapsulation methods, each specifically engineered in view of the requirements of each drug's properties and production setup. 5,6 Microencapsulation can be benefited in modifying and retarding drug release and improving its absorption. In pharmaceutical sustained release formulations, the advantage of microcapsules lies in the wide distribution throughout the Gastrointestinal tract (GIT).…”
Section: Introductionmentioning
confidence: 99%